Eastern Imports in the Marche Region during the Roman Age - Di Michele, Dario (O T I V M, 2021)
Recent studies of Roman pottery led in various contexts of the Marche region (Italy) have certainly enriched the cognitive heritage. Nevertheless, many gaps remain, due to the lack of publication of key sites (e.g. Ancona). This contribution aims to outline, without pretensions of exhaustiveness, the state of studies on imports of eastern pottery in the Marche region from 3th BC to 7th century AD, using well-known studies, such as those of Liliana Mercando, but also data provided by the most recent searches in this field.